TINGKAT PENGETAHUAN MAHASISWA S1 AKUNTANSI TERHADAP PERUBAHAN PSAK - Efritania, Riyanda (Jurnal Akuntansi AKUNESA, 2014)
The aims of this study was to determine the student knowledge level majoring in accounting about changes of PSAK. This study uses primary data collected by distributing questionnaires to the respondents. The respondents of this study are undergraduate students majoring in accounting, State University of Surabaya who already take Financial Accounting subject. The results of this study indicate that students find a difficulty to understand PSAK with IFRS convergence. Students motivated to further deepen their knowledge when go public companies prefer to choose the students who have better knowledge about PSAK based on IFRS.Keywords: knowledge level, student, PSAK